Новые виды клещей семейства Antennoseiidae (Parasitiformes, Mesostigmata) - Балан, П.Г. (Вестник зоологии, 1988)
Two species of the genus Antennoseius (s. str.) are described as new from Tadjik SSR: (A. (A.) shcherbakae sp. n. and A. (A.) ghilarovi sp. n. Type material is deposited in the Schmalhausen Institute of Zoology (Kiev).